Membentuk Karakter Anak Usia Dini Dengan Pendekatan Islam - Nuraeni, Dini (Yayasan Darusssalam Bengkulu, 2021)
The aim of the research is to describe the character formation of early childhood carried out by teachers at TK Azzahra, Bengkulu City with supporting and inhibiting factors. The method used in the research uses descriptive qualitative methods. Data collection techniques used were interviews, observation and documentation. Data validity techniques use source and data triangulation. The results of the research conducted show that it is very important for character education in early childhood in the Islamic approach to form moral knowledge (moral knowing), moral personality (moral feeling), moral character (moral acting). With an Islamic education approach, it is given by teachers or parents to children with Islamic teaching in accordance with the child's morals and heart. In implementing children's character at Azzahra Kindergarten, teachers will teach children to say thank you, when someone gives a gift or reward, say greeting and kiss the hands of teachers and parents when they arrive at school, answer greetings when someone else gives greetings, be kind to other students and be polite to teachers and other students.